Decreased sensitivity of several anticancer drugs in TMEPAI knockout triple-negative breast cancer cells (Medical Journal of Indonesia, 2019)
BACKGROUND Transmembrane prostate androgen-induced protein (TMEPAI) was reported to be highly amplified in the majority of patients with triple-negative breast cancer (TNBC). TMEPAI is related to poorer prognosis, limited treatment options, and prone to drug resistance compared with other proteins. One of the established markers to determine cancer resistance to drugs is the increased expression levels of drug efflux transporters. However, the role of TMEPAI in cancer resistance to drugs has not been elucidated. This study was aimed to investigate whether TMEPAI participates in cancer resistance to drugs by regulating drug efflux transporters. METHODS TMEPAI knockout (KO) cells were previously developed from a TNBC cell line, Hs578T (wild-type/WT), using a CRISPR-Cas9 system. The expression levels of drug efflux transporters were determined in Hs578T-KO and Hs578-WT by quantitative reverse transcriptase polymerase chain reaction. Cytotoxic concentration 50% (CC50) of several anticancer drugs (doxorubicin, cisplatin, and paclitaxel) were determined in the two cell lines via 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium assay. RESULTS The results showed that the mRNA expression of P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) was significantly increased in Hs578T-KO compared with that in Hs578T-WT cells. CC50 of several anticancer drugs investigated (doxorubicin, paclitaxel, and cisplatin) in Hs578T-KO cells was higher than that in Hs678-WT. CONCLUSIONS TMEPAI participated in the regulation of mRNA expression levels in drug efflux transporters (P-gp, BCRP, and multidrug resistance-associated protein 1). Further studies are necessary to confirm whether this finding might be dependent on the development of cancer cell sensitivity to anticancer agents.